The 230 GHz Variability of Numerical Models of Sagittarius A*. II. The Physical Origins of the Variability - Ho-Sang Chan; Chi-kwan Chan (The Astrophysical Journal)
We continue our previous work, H.-S. Chan et al., to investigate how variations in the electron temperature prescription parameter, R _Low , influence the 3 hr variability at 230 GHz, M _Δ _T , in magnetically arrested disk (MAD) models of Sagittarius A* (Sgr A*), through analyzing a series of general-relativistic magnetohydrodynamics and ray-tracing simulations. For models with a black hole spin a  > 0, we discovered that increasing R _Low renders the photon ring more optically thick, obscuring the varying accretion flows that contribute to the variability. However, as R _Low increases further, MAD flux eruptions become more pronounced, compensating for the decrease in M _Δ _T . For models with spin a  < 0, although a higher R _Low also increases the optical thickness of the fluid, voids within the optically thick gas fail to cover the entire photon ring. Similarly, flux eruptions become more prominent as R _Low increases further, contributing to the observed rise in M _Δ _T relative to R _Low . For black holes with spin a = 0, although the effect of increasing optical depth is still present, their 230 GHz light curves, and hence M _Δ _T , are insensitive to changes in R _Low . Furthermore, we found that the variability of the 230 GHz light curves at R _Low  = 1 might correlate with fluctuations in the internal energy of the gas near the black hole, and we listed potential causes and solutions to the over-variability problem. Our findings highlight potential approaches for refining M _Δ _T to better align with observations when modeling Sgr A*.